Reducing Defects Using DMAIC Methodology in an Automotive Industry - Imansuri, Febriza; Chayatunnufus, Tasya; Safril, Safril; Sumasto, Fredy; Purwojatmiko, B. Handoko; Salati, Dianasanti (Universitas Ahmad Dahlan, 2024)
Quality is when it meets the wants and expectations of customers or even exceeds them. Every company must raise the quality of its current products and services. A complete and adaptable approach for establishing, maintaining, and maximizing company success is Six Sigma. Define, Measure, Analyze, Improve, and Control (DMAIC) is one of the tools used to implement Six Sigma. PT. KRM is one company engaged in the automotive sector, which produces Colt Diesel trucks. This research focuses on the welding processes. Defective products were found in as much as 5% of total production, exceeding the company's target of 3%. This research was conducted to determine the process capability based on product defects with the Six Sigma DMAIC method approach, then to find out the proposal for implementing quality control by analyzing the causes of defects in the production process and then looking for continuous improvement with the 5W+1H concept. The improvement was made to decrease the DPMO value of 4.496 and increase the sigma value of 0.19. This study demonstrates how the Six Sigma DMAIC approach can improve the quality of the cabin production process for the part side outer pillar LH. This case can help company managers apply Six Sigma methods to solve complex problems in other processes.